Television and Babies’ Sleep - Kristen McDanel; Suzanna Smith (EDIS, 2012)
“There are a number of video and television programs that have been made for children under the age of three. At times it may be fun to watch your baby or toddler bounce or dance along with the characters on the screen. Many busy caregivers also use these shows to give themselves a little time for a needed break or to prepare a meal or tidy up. However, watching television may not be best for your baby or toddler’s sleep.” This 2-page Family Album Radio transcript was written by Kristen McDanel and Suzanna Smith, and published by the UF Department of Family, Youth and Community Sciences, August 2012.